CD271+, CXCR7+, CXCR4+, and CD133+ Stem/Progenitor Cells and Clinical Characteristics of Acute Ischemic Stroke Patients - Gójska-Grymajło, Anna (Neuromolecular Med, 2018)
Ischemic stroke causes mobilization of various groups of progenitor cells from bone marrow to bloodstream and this correlates with the neurological status of stroke patients. The goal of our study was to identify the activity of chosen progenitor/stem cells in the peripheral blood of acute ischemic stroke patients in the first 7 days after the incident, through associations between the levels of the cells and clinical features of the patients. Thirty-three acute ischemic stroke patients and 15 non-stroke control subjects had their venous blood collected repeatedly in order to assess the levels of the CD45–CD34 + CD271+, the CD45–CD34 + CXCR4+, the CD45–CD34 + CXCR7+, and the CD45–CD34 + CD133+ stem/progenitor cells by means of flow cytometry. The patients underwent repeated neurological and clinical assessments, pulse wave velocity (PWV) assessment on day 5, and MRI on day 1 and 5 ± 2. The levels of the CD45–CD34 + CXCR7+ and the CD45–CD34 + CD271+ cells were lower in the stroke patients compared with the control subjects. Only the CD45–CD34 + CD271+ cells correlated positively with lesion volume in the second MRI. The levels of the CD45–CD34 + CD133+ cells on day 2 correlated negatively with PWV and NIHSS score on day 9. The patients whose PWV was above 10 m/s had significantly higher levels of the CD45–CD34 + CXCR4+ and the CD45–CD34 + CXCR7+ cells on day 1 than those with PWV below 10 m/s. This study discovers possible activity of the CD45–CD34 + CD271+ progenitor/stem cells during the first 7 days after ischemic stroke, suggests associations of the CD45–CD34 + CD133+ cells with the neurological status of stroke patients, and some activity of the CD45–CD34 + CD133+, the CD45–CD34 + CXCR4+, and the CD45–CD34 + CXCR7+ progenitor/stem cells in the process of arterial remodeling. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12017-018-8494-x) contains supplementary material, which is available to authorized users.